1999
DOI: 10.1007/s004380051063
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and mapping of sequence-tagged microsatellite sites in the chickpea (Cicer arietinum L.) genome

Abstract: A size-selected genomic library comprising 280,000 colonies and representing approximately 18% of the chickpea genome, was screened for (GA)n, (GAA)n and (TAA)n microsatellite-containing clones, of which 389 were sequenced. The majority (approximately 75%) contained perfect repeats; interrupted, interrupted compound and compound repeats were only present in 6%-9% of cases. (TAA)-microsatellites contained the longest repeats, with unit numbers from 9 to 131. For 218 loci primers could be designed and used for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
207
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(228 citation statements)
references
References 29 publications
19
207
1
1
Order By: Relevance
“…Chickpeas yields were improved since the introduction of winter chickpeas, during the 1999-2000 cropping season, with an average yield that went up from 6.2 quintals ha -1 in 1987-1999to 7.45 quintals ha -1 in 1999-2007(DGPA, 2008. New varieties were developed by researchers at ICARDA (International Center for Agricultural Research in the Dry Area) using a new concept of winter sowing that allows chickpeas to take advantage of winter rains to improve vegetative growth, biomass and yield production (Singh & Hawtin, 1979;Ben Mbarek, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Chickpeas yields were improved since the introduction of winter chickpeas, during the 1999-2000 cropping season, with an average yield that went up from 6.2 quintals ha -1 in 1987-1999to 7.45 quintals ha -1 in 1999-2007(DGPA, 2008. New varieties were developed by researchers at ICARDA (International Center for Agricultural Research in the Dry Area) using a new concept of winter sowing that allows chickpeas to take advantage of winter rains to improve vegetative growth, biomass and yield production (Singh & Hawtin, 1979;Ben Mbarek, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Chowdhary et al (2002) compared chickpea and other pulses for the level of polymorphism with RAPD and reported low polymorphism in chickpea as compared to other pulses. Cultivated chickpea is characterized with limited genetic variability therefore, inter-specific crosses have been utilized for the construction of linkage maps (Simon and Muelbaur, 1997;Winter et al, 1999). Despite low level of polymorphism obtained, in the present study, three primers, OPP9, OPC5 and OPC14 differentiated between Kabuli genotypes (ILC482, ICCV2, Pb1) and Desi genotypes (Dasht, Balkasar) of chickpea.…”
Section: Discussionmentioning
confidence: 60%
“…It is suggested that STMS markers be used for variability studies in cultivated chickpea as RAPD markers are unable to reveal the DNA polymorphism that is responsible for genotypic variation with respect to agro-morphological traits. STMS markers have been extensively used for mapping in chickpea (Winter et al, 1999). The grouping of genotypes in two dandrograms constructed on the basis of RAPD data and morphological data did not reveal any relationship with each other.…”
Section: Discussionmentioning
confidence: 96%
“…Kỹ thuật này cũng được sử dụng nhiều trong nghiên cứu đa dạng di truyền, phân tích genome [86], lập bản đồ di truyền [51,198] và nhận biết giống [47].…”
Section: Kỹ Thuật đA Hình độ Dài đOạn Nhân Chọn Lọc (Amplified Fragmeunclassified